Money creation and commercial banks’ money lending activity through the accounting treatment: stakeholders’ perceptions in Malaysia - Hossain, Md Shamim; Abdul Latiff, Ahmed Razman; Osman, Mohammad Noor Hisham (Emerald Publishing, 2022)
Purpose: The purpose of this study is to explore stakeholders’ perceptions on money creation and the impact of the accounting treatment for commercial banks’ money lending activity in Malaysia. Design/methodology/approach: A phenomenological approach was used to examine the stakeholders’ perceptions through experience-sharing. A semi-structured interview approach was used to collect the data. Ten individuals from different stakeholder groups have been interviewed with their prior consent. For the data analysis, the current study adopted the inductive thematic approach. Findings: Perceptions on money creation are influenced by the informants’ understanding and awareness of the research issue. Informants have agreed on the accounting treatment (debit loan and credit deposits) but explained the impact of this accounting treatment differently. The accounting treatment creates an opportunity for the commercial banks to create money as they want, and hence, the excess created money can create inflation and threat for the potential financial crisis. On the contrary, it is argued that money creation results from the systematic approach of the fractional reserve banking (FRB) in Malaysia. In addition, this money creation is not a threat to the economy as long as there is a strong controlling role of Bank Negara Malaysia (BNM). Research limitations/implications: Stakeholders’ perception indicates that awareness of the research issue can be a cause of crucial consequence for money lending activity. Moreover, this study may stimulate the chief regulatory body such as BNM, the central bank of Malaysia, to be more cautious in controlling the commercial banks’ money lending activity to prevent the potential future crisis. Furthermore, findings may help to explain the conflicting concept between the textbook explanation for FRB and current commercial banks’ money lending practice through the accounting treatment. Originality/value: Monitoring and controlling of money creation and commercial banks’ money lending activity by BNM can be benefited from the stakeholders’ perceptions on this research issue. Because this is the first time study of the stakeholders’ perceptions on money creation and commercial banks’ money lending activity in Malaysia and hence, findings of this study may be worked as the input in the process of monitoring and controlling the money creation activity in Malaysia.